(untitled) (Journal of Naval Architecture and Marine Engineering, 2024)
Over the past several decades, there has been an extreme increase in high temperatures across the global ocean, termed Marine Heatwaves (MHW). MHWs have devastating impacts on human life and ecological systems, affecting biodiversity, fisheries, and aquaculture. Due to extreme heat, mass extinctions of various species and marine habitats such as seagrass and coral reefs are occurring. It is crucial to investigate how the dynamics and trends of MHWs might change using available data from models and satellites to better mitigate future predicaments. This study presents a detailed analysis of MHWs, including an examination from 2001 to June 2024 in a low-lying country like Bangladesh. A step-by-step procedure is shown to calculate MHWs using a computer program (MATLAB). This study also shows a recent increasing trend in MHW, predicting an increased amount of land loss for low-lying countries.